Peak oxygen consumption is associated with the inotropic reserve in patients with heart failure with reduced ejection fraction undergoing cardiopulmonary testing. (3rd October 2022) - Soulaidopoulos, S; Stamoulopoulos, I; Fragoulis, C; Kalos, T; Xydis, P; Konstantinou, K; Chrysohoou, C; Tsioufis, K
Abstract: Background: The role of cardiopulmonary exercise testing (CPET) in the prognostic evaluation of heart failure with reduced ejection fraction (HFrEF) is powerful and well-established. Nevertheless, the value of CPET in predicting left ventricular inotropic reserve in HFrEF remains unknown. Purpose: The investigation of possible associations between CPET variables and left ventricular contractile reserve in patients with HFrEF. Methods: Consecutive patients aged ≥18 years old with a diagnosis of heart failure and a left ventricular ejection fraction ≤40%, as assessed by echocardiography, were prospectively enrolled. Demographic and clinical data were recorded. All subject underwent CPET with either a Bruce or a modified Bruce protocol. Peak oxygen consumption (VO2), carbondioxide production (VCO2), minute ventilation to carbon dioxide production (VE/VCO2) slope, minute ventilation (VE), and VO2/heart rate (HR) values were calculated, while hemodynamic parameters during the test were also measured. Results: In total, 191 patients with HFrEF were included in the analysis. The mean age was 58.8±11.8 years and 30 (15.7%) patients were women. Ischemic heart disease was the etiology of HFrEF in 101 (52.9%) patients, whereas 90 (47.1%) patients had a history of dilated cardiomyopathy. The mean exercise time was 7.6±.3 minutes. Mean peak VO2 and VE/VCO2 slope values were calculated at 19.1±6.1 ml kg –1 min –1 and 43.7±10.1, respectively. According to peak VO2 values, 70 patients (37.2%) were in Weber class A, 57 (29.8%) in class B, 48 (25.1%) in class C and 15 (7.9%) in class D. In univariate analysis, the change between rest and peak systolic blood pressure (ΔSBP), which is considered to reflect the left ventricular inotropic reserve, was positively correlated to the peak VO2 (p<0.001), the total pulmonary ventilation (VE) (p<0.001) and the peak heart rate during exercise (p=0.02). In multivariable analysis, peak VO2 was independently, linearly associated with the ΔSBP during CPET (Figure 1) (β=0.661, p=0.022). In Roc analysis, it was found that a cut-off value for peak VO2 of 16 ml kg –1 min –1 exhibits 64% sensitivity and 60% specificity in predicting a ΔSBP>40mmHg during exercise (area under the curve: 0.657, p<0.001 – Figure 2). Conclusion: The peak oxygen consumption during cardiopulmonary testing represents an acceptable predictor of inotropic reserve in patients with HFrEF. Funding Acknowledgement: Type of funding sources: None.